Public Health since the beginning: Neonatal incubators safety in a clinical setting - Mattia Fattorini; Giuseppe Buonocore; Daniele Lenzi; Sandra Burgassi; Rosa M.R. Cardaci; Klaus P. Biermann; Gabriele Cevenini; Gabriele Messina (Elsevier, 2018)
Background: The role of environmental cleaning as an effective measure to contain the diffusion of Healthcare Associated Infections (HAIs) has already been demonstrated. Among medical devices, neonatal incubators have been recognized as a source of pathogens involved in the spread of HAIs. Aim of the study was to assess the efficacy of a disinfection protocol for neonatal incubators. Methods: The cross sectional study took place in the "Neonatal Pediatric Unit" of the Teaching Hospital of Siena: twenty incubators, used for critical newborns, were swabbed in 13 sampling points before and after the implementation of the disinfection protocol. Sanitation procedures were performed by trained staff, implementing the product Umonium38® Neutralis as disinfectant. Different culture media for the identification of the microbial contamination were adopted: plates were incubated for the proper time and the results were referred to Colony Forming Units (CFUs)/swab per point. Descriptive statistical analysis was performed. It was also evaluated the 95% confidence interval (C.I.) of the mean and the percentage of CFUs reduction by the bootstrap bias corrected and accelerated resampling method. Results: Matched points analyzed were 313. The average CFUs percentage of reduction was 93.5% [C.I. 90.6-95.9%]: it was higher, 97.0% [C.I. 94.1-99.1%], in points placed inside the incubators structure compared to the 88.4% [C.I. 83.6-93.0%] obtained outside. Conclusion: The disinfection protocol achieved good results. Routine surveillance and supervision of the various aspects of the disinfection processes (procedures, staff and disinfectants) could guarantee a safe environment during the first days of babies' life, avoiding harmful conditions for the newborns' health. Keywords: Healthcare Associated Infections, Disinfection, Neonatal incubators, Italy